Coetaneous Presentation of Oral Leukoplakia and Oral Submucous Fibrosis with High Grade Dysplasia and Its Management with Lasers: A Case Report - R, Preethi; T, Malarkodi; Krishnamurthy, Arvind; Warrier S, Aravind (International Journal of Innovative Research in Medical Science, 2021)
Oral potentially malignant disorders (OPMD) are diverse lesions associated with an increased likelihood for malignant transformation to oral cancer. The most frequently encountered OPMD in clinical practice are Oral Leukoplakia and oral submucous fibrosis (OSMF). The use of tobacco is consistently linked with leukoplakia and areca/betel nut with OSMF. Histopathological features of oral epithelial dysplasia, its varying grades are of immense clinical significance to evaluate its ability for malignant transformation. We report a case of homogenous leukoplakia and OSMF, two oral potentially malignant disorders occurring at the same site with high-grade dysplasia and its management using lasers.